GENETIC MARKERS OF MYOCARDIAL FIBROSIS: OPPORTUNITY TO PREDICT ADVERSE OUTCOMES IN AORTIC STENOSIS - Т. A. Tipteva; О. S. Chumakova; A. N. Brovkin; A. G. Nikitin; N. Е. Reznichenko; D. A. Zateyshchikov (Российский кардиологический журнал, 2018)
Aim. To evaluate the influence of genetic markers of inflammation and fibrosis on survival rate of patients with non operated aortic stenosis (AS). The search for novel prognostically adverse factors in calcinated AS patients with none surgical treatment remains actual.Material and methods. During 2,1±0,11 years, 191 patient has been followed up (28,6% males, 78,0±0,60 y. o.) with a “natural course” of AS (aortic valve area ≤2,0 cm2). All fatal outcomes (FO) were collected. Then the clinical, biochemical and echocardiographic parameters were compared, genotypes frequencies and alleles of mononucleotide polymorphisms (MNP) G(-238)A and G(-308)A gene TNF, С(-592)A gene IL-10, Arg25Pro gene TGFβ1 in groups with FO and with none. Life duration towards FO was evaluated.Results. Fatal outcomes were registered in 71 (37,2%) of patients. Death causes were: myocardial infarction in 5, stroke in 8, sudden death in 10, chronic heart failure (CHF) in 29, thromboembolism in 5, non-cardiac cause in 14. Independent factors associated with FO were: presence of CHF III-IV FC NYHA, creatinine level, aortic valve area, myocardial mass index of the left ventricle and carriage of allele Pro MNP Arg25Pro gene TGFβ1 (р<0,05). Associations of MNP G(-238)A and G(-308)A gene TNF, as MNP С(-592)A gene IL-10 with FO were not found. Mean life duration before death in Pro MNP Arg25Pro gene TGFβ1 carriers was 468,6±99,62 days versus 617,6±77,19 days in non-carriers (р<0,05).Conclusion.  The carriage of allele Pro MNP Arg25Pro gene TGFβ1 can be regarded as one more predictor of fatal outcome in patients with non-operated AS. It is clear that LV myocardial fibrosis, developing in AS patients, might be a factor significantly influencing prognosis.